KARAKTERISTIK TINDAK PIDANA PASAR MODAL - Sultan Syahril A Kh (Jurnal HUKUM BISNIS, 2022)
National economic goals that are able to grow stably and sustainably, create broad and balanced employment opportunities in all sectors of the economy, as well as provide equitable welfare to all Indonesians General explanation of Law No. 8 of 1995 concerningThe Capital Market (hereinafter referred to as the Capital Market Law) explicitly explained that "the capital market aims to support the implementation of national development in the context of increasing equity, growth, and national economic stability towards improving people's welfare". as stated in article 4 of Law Number 21 of 2011 concerning the Financial Services Authority (OJK), one of the objectives of the establishment of OJK is to protect the interests of consumers and the public against violations of laws and regulations in the financial sector which are under the authority of the OJK